Cohort size and the academic labor market - Stapleton, David C. [Verfasser] (My University, 1989)
"Educational policymakers have long been concerned that baby bomms and busts alternately cause shortages and surpluses in academic labor markets. These concerns have been supported by models which purport to forcast the effects of change in cohort size on the academic labor market. In this paper it is argued that policymakers should be more skeptical of such forecasts. The basis for the argument is a detailed analysis of a model of the academic labor market for ecomists. The inescaple conclusion is that forecasts from such models provide little, if any, support for policies designed to offset the impact of change in cohort size on the academic labor market." (author's abtract) ((en)) Der Beitrag befasst sich mit der Prognostik zu den Chancen von Akademikern auf dem Arbeitsmarkt. Insbesondere wird auf den Einfluss der jeweiligen Kohortengrössen von Hochschulabsolventen eingegangen. Die Überlegungen werden durch eine Analyse des Arbeitsmarktes für amerikanische Wirtschaftswissenschaftler konkretisiert. (IAB)
Kohortengrösse und Akademikerarbeitsmarkt
Keywords: P 2.6 Hochschulabsolventen; T 3 Forschungsmethoden; S 6.4 Dienstleistungsberufe; G 2.4.3 Privater & Familiärer Wandel; Akademiker; Arbeitsmarkt; Kohortenanalyse; Prognostik; Wirtschaftswissenschaftler; Geburtenentwicklung; Auswirkung; Arbeitsmarktchance; Quantitative Angaben